Effect of hydrogel and irrigation scheduling on water use efficiency and productivity of Indian mustard (Brassica juncea L.) in Jammu region (Journal of Oilseed Brassica, 2026)
A field experiment was conducted to study the effect of irrigation scheduling and hydrogel application in Indian mustard (Brassica juncea L.) of Jammu region, India. The application of hydrogel @ 5.0 kg/ha and irrigation scheduling at 0.8 and 0.6 IW/CPE resulted in significant increase in the yield attributes, oil yield and seed yield of Indian mustard during first and second year of experimentation respectively besides concomitant increase in the water use efficiency of Indian mustard than control and other treatments in comparison. However, no application of hydrogel and irrigation scheduling at 0.4 IW/CPE was found to be the most economical treatment than other treatments in comparison